Pilomatrixoma Pathology Description of Squamous Cell Carcinoma: A Case Report - Rantapina Kurnia Sari; Kiki Ahmad Rizki; Birgitta Maria Dewayani (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Pilomatrixoma is a benign neoplasm derived from hair follicles, and it rarely happens. Some cases were misdiagnostic with another skin lesion. One of them was squamous cell carcinoma (SCC). This study aimed to describe the pilomatrixoma pathology description of squamous cell carcinoma. Case presentation: A man, 72 years old admitted to the hospital with a chief complaint lump on his chin that penetrated into his mouth near the mandible gum. A lump had an irregular surface, hyperemic ulcer, bled easily, and penetrated into the mouth near the mandible gum. The size was 5x8x5cm, tenderness (+), and fixed with the mandible. There was no enlargement of neck nodes. The pathology description from the incision biopsy was pilomatrixoma. Wide excision, segmental mandibulectomy, and frozen section were performed on the patient, and the result was keratinizing SCC well differentiated. Conclusion: A man 72 years old with a lump on his chin was diagnosed with pilomatrixoma, a benign neoplasm that occurs in hair follicles and is a rare case.